2009
DOI: 10.3892/mmr_00000231
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of carcinogen-induced rodent lung tumors: Involvement of microRNA expression and Krαs or Egfr mutations

Abstract: Abstract. Genetic and epigenetic alterations play a key role in lung carcinogenesis, and a high frequency of Kras and epidermal growth factor receptor (Egfr) mutations have been observed in human lung cancers. recent evidence indicates that the expression of specific microRNAs (miRNAs) may be involved. in rodent lung carcinogenesis models, Kras mutations are frequently observed, whereas genetic alteration of the Egfr gene is generally rare. Since little is known regarding the involvement of mirnas in rodent lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Some studies have suggested that SP-A might have a role in suppressing lung cancer progression, and SP-A expression by tumor cells leads to recruitment and activation of NK cells and tumor-associated macrophages 19 . In another study, activating mutations of the Kras gene at codon 12 were reported in 47% of lesions induced by DHPN in the F344 rat 8 . Overexpression of oncogenic Kras leads to activation of the NF-κB pathway, which appears to be required for the development of tumors in a mouse model of lung adenocarcinoma 30 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some studies have suggested that SP-A might have a role in suppressing lung cancer progression, and SP-A expression by tumor cells leads to recruitment and activation of NK cells and tumor-associated macrophages 19 . In another study, activating mutations of the Kras gene at codon 12 were reported in 47% of lesions induced by DHPN in the F344 rat 8 . Overexpression of oncogenic Kras leads to activation of the NF-κB pathway, which appears to be required for the development of tumors in a mouse model of lung adenocarcinoma 30 .…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that activating mutations of the Kras gene at codon 12 are detected in almost 50% of rat lung neoplastic lesions induced by a carcinogen 8 . Furthermore, we previously examined the lung toxicity of fine particles of various materials in an in vivo bioassay using an IT approach 5 , 7 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, an EGFR mutation was detected, while a K-ras mutation was not detected. While it is unclear how mutations of EGFR and other molecular alterations are related to the mechanisms involved in pulmonary tumorigenesis in mice, both genetic and epigenetic factors are known to be important for tumorigenesis (39). In this case, it is impossible to resolve the mechanism of the phenomenon based on only one tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to provide further clarification to these possible oncogenic inputs required, we performed chemical carcinogenesis using two well known lung carcinogens, DHPN and urethane, that cause Kras activation [19, 20, 22]. We observed that under our experimental conditions DHPN is insufficient to cause tumor development in control mice, probably due to the mixed background of the strain used [44], although a potential role of p107 deficiency can not be discarded at present.…”
Section: Discussionmentioning
confidence: 97%
“…DHPN, a potent mutagen and a wide-spectrum carcinogen in rodents induces lung tumors when given in drinking water [16–18]. Mutational activation of Kras has been described in these rodent lung tumors [19, 20]. Urethane (ethyl carbamate), a component of various food products and cigarette smoke, induces the formation of lung tumors in animal models.…”
Section: Introductionmentioning
confidence: 99%